Determination of poly[(2-phenyl-1,3dioxolane-4-yl) methyl methaerylate-co-glycidyl methacrylate]-probe interactions by inverse gas chromatography - Ilter, Z; Kaya, I; Açikses, A (Taylor & Francis Inc, 2004)
In this study, we determined the thermodynamic properties [such as the adsorption enthalpy, DeltaH(a), the sorption enthalpy, DeltaH(1)(s), sorption free energy, DeltaG(1)(s), sorption entropy, DeltaS(1)(s), the partial molar free energy, DeltaG(1)(infinity), and the partial molar heat of mixing (DeltaH(1)(infinity))] at infinite dilution for the interactions of poly[(2-phenyl-1,3-dioxolane-4-yl) methyl methacrylate-co-glycidyl methacrylate] poly (PDMMA-co-GMA) with alcohols and n-alkanes by the inverse gas chromatography method in the temperature range of 343-463K. According to the specific retention volumes (V-g(0)), the weight fraction activity coefficients of solute probes at infinite dilution, Omega(1)(infinity), and Flory-Huggins interaction parameters (chi(12)(infinity)) between poly (PDMMA-co-GMA)-solvents were determined in 423-463K. According to Omega(1)(infinity) and chi(12)(infinity), selected alcohols and n-alkanes were found to be nonsolvent for poly (PDMMA-co-GMA) between 423 and 463K. Also, the solubility parameters, delta(2), of poly (PDMMA-co-GMA) were found to be 22.15 (J cm(-3))(0.5) and 25.50 (J cm(-3))(0.5) from slope and intercept of [(delta(1)(2)/RT) - chi(12)(infinity)/V-1) = (2delta(2)/RT)delta(1)-delta(2)(2)/RT equation, at 443K, respectively. The glass transition temperature (T-g) of the poly (PDMMA-co-GMA) was found to be 370 and 367K, respectively, by inverse gas chromatography and differential scanning colorimetry (DSC) techniques.
Keywords: poly[(2-phenyl-1,3-dioxolane-4-yl) methylmethacry-late-co-glycidyl methacrylate]; inverse gas chromatography; polymer-solvent interactions